Phytochemical Screening, Antioxidant and Antibacterial Activities of the Root Extract of Cyphostemma adenocaule (Steud. ex A. Rich.) Wild & R.B.Drumm - Abdulbasit Haliru Yakubu; Mohammed Mustapha Mohammed; Abdulqadir Bukar Bababe; Hassan Yesufu Braimah (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2021)
Plant secondary metabolites have provided important bioactive principles for developing new lead compounds. Within their confinement, they exhibit unique chemical diversity, which influences their diverse biological properties. The Vitaceae family is known for its potent antioxidant and antibacterial phytoconstituents, among other biological properties. Cyphostemma adenocaule is one of the family members explored for its ethnomedicinal properties. This study undertook the evaluation of the phytochemical, antioxidant, and antibacterial properties of the root extract of Cyphostemma adenocaule. Preliminary phytochemical screening revealed the presence of flavonoids, alkaloids, carbohydrates & glycoside, saponins, and tannins. The methanol root extract had the highest activity in the DPPH assay, providing IC50 (50% inhibition) of 10.87µg/ml, followed by n-Hexane (IC50 74.10µg/ml) and chloroform (IC50 74.31µg/ml) extract. In the antibacterial assay, the chloroform extract was active against E. coli (24.00±0.15) and had moderate activity against Staph. aureus (12.5±0.18). The n-Hexane extract was completely inactive against the test organisms while the methanol extract showed poor activity against the test organisms. The present study adds to the existing literature on Cyphostemma adenocaule with scientific evidence into its biological properties.